Detecção de fatores de virulência e do gene de resistência blaKPC2 em isolados de Klebsiella pneumoniae de humanos e de animais domésticos e silvestres - Makino, Herica (2022)
Klebsiella pneumoniae belongs to Enterobacteriaceae family, which is known by the ability to developed mechanisms regarding pathogenicity and antimicrobial resistence. The aim of this study human, domestic and wild animals was to detect the thevirulence factors and the blaKPC-2resistance gene from K. pneumoniae isolates in the state of Mato Grosso. In total, 85 samples were analyzed of which, 69 were from animals and 16 from humans, through detection of genes by polymerase chain reaction (PCR) entB, fimH, mrkD, wabG, ugE, kfuBC, magA, k2A genes, rmpA and blaKPC-2. In human isolates, the most detected virulence factors were ugE (62,5%), entB (43,7%), fimH (31,2%) and wabG (31,2%). In humans, the blaKPC-2 gene was detected in three samples. In domestic animals, the most detected genes were entB (65,8%), fimH (58,5%) and wabG (48,8%), while in wild animals they were entB (78,6%), wabG (71,4%) and ugE (57,1%). In animals, the blaKPC-2 gene was detected in a sample. The data presented demonstrate a large distribution of isolates containing virulence factors and the blaKPC-2 resistance gene in the state of Mato Grosso, representing a threat and a problem both in Veterinary Medicine and in Public Health due to possible dissemination and transfer of genes from resistance and virulence among pathogens.